Simulating the Income Distribution Effects of the 1988-1992 Tariff Reduction Using the APEX Model - Caesar B. Cororaton (Philippine Institute for Development Studies (PIDS), 1996)
Accounting for the 1988-1992 trade reforms undertaken by the government, this paper simulates its economic effects in nominal tariff rates and implicit tariff rates using the APEX model/computable general equilibrium model of the Philippine economy
Keywords: 330